Mean length of utterance and syntactic complexity in the speech of the cerebral plasied children - Nandini Iyer (Journal of All India Institute of Speech and Hearing)
The present study was aimed at describing the mean length of utterance and syntactic complexity in the cerebral palsied children, a group of children with neuromuscular involvement due to CNS dysfunction. 20 normal children and 10 cerebral palsied children were considered in the age range of 4-11 years. All the children had average or above average intelligence and normal hearing. They came from a middle socio-economic background. In the cerebral palsy group, 8 spastics and 2 atheoid were studied A language sample consisting of spontaneous and narrative/elicited utterances was recorded from each of these 30 children.